World status of wild Rangifer tarandus populations - Williams, T. Mark; Heard, Douglas C. (Rangifer, 1986)
We recognized 184 herds of wild Rangifer tarandus, 102 in North America, 55 in Europe, 24 in Asia and 3 on South Georgia. Seventy-five percent of the world population of 3.3 to 3.9 million animals occurred in nine herds. All seven herds larger than 120 000 animals were censused by some means of aerial photography and all were increasing. Herds between 20 000 and 120 000 were most often censused using aerial strip transect methods, while total counts were usually employed to census smaller herds. The most pronounced changes in Rangifer herd status between 1979 and 1985 occurred in North America where population "estimates for five herds increased by a total of about one million animals. Part of this increase is attributable to a change from visual to photographic surveys. Eighty-three percent of North American, 88% of European, and 68% of Asian herds were stable or increasing.